Undiagnosed movement disorder in speed skating: a possible form of task specific dystonia - Nijenhuis, B. (ISBS Proceedings Archive (Michigan), 2019)
This study aimed to investigate the bio-mechanics of a mysterious and undiagnosed movement disorder appearing in the Netherlands among expert speed skaters known as `zwabbervoet` or, skater`s cramp. An unpublished manuscript looking at 5 affected skaters indicates that the disorder may be a form of task specific dystonia. Using a novel tailor-made program for analyzing speed skating, this study looked at the kinematic features of skater`s cramp. The results showed skater`s cramp was person specific, that it had a clear, consistent asymmetry that was predictable across multiple gait cycles irrespective of speed or intensity of skating. A more in depth analysis combining electromyography and force measurement with the current analysis is in development to further investigate the task specificity of this disorder.